Analysis of the Early Warning System for the Potential Bankruptcy of Rural Banks in Depok: Analisis Sistem Peringatan Dini Terhadap Potensi Kebangkrutan Bank Perkreditan Rakyat di Depok - Farhan Haidir Alwi; Heri Abrianto (Politeknik Negeri Jakarta, 2022)
An early warning system is one of the tools used to analyze financial ratios and process it into useful information to be used as a monitoring system for the company's financial performance. This study aims to determine whether the ratio of NPL, LDR, ROA, and KPMM has an effect on the bankruptcy of BPR in Depok. This study uses secondary data published by the Financial Services Authority from 2017 to 2021. The determination of the sample uses the purposive sampling method. This study uses the Logit Regression method to predict bankruptcy and analysis of the influence of factors. The result of this study is that ROA has a significant effect on the bankruptcy of BPR in Depok, while NPL, LDR, and KPMM have no significant effect on the bankruptcy of BPR in Depok.